How is Quality in Homecare Services Created? A Qualitative Study of Health Professional Perspectives - Suprapto, Suprapto; Andi Latif, Sarifudin; Nurhanifah, Dewi; Yunus, Muh; Ajeng Wijayanti, Lumastari (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2025)
Nursing services in home healthcare are becoming increasingly important as the number of patients requiring long-term care and post-inpatient care increases. The standard of nursing care delivered at home is crucial for the well-being of both patients and their families. This study investigates how health professionals perceive the creation of quality nursing services in home healthcare. Methodology: This study uses a qualitative approach with an in-depth interview method. Ten health professionals, including nurses, doctors, and home health care managers, were selected as participants through purposive sampling. The data were analyzed using thematic analysis methods to identify relevant themes and subthemes. Results: The results show that the quality of nursing services at home is created through several key factors: competency and training of nurses, effective communication between health teams, involvement of families in care, availability of resources, and clear management and policy support. Nurse competence and training are considered the most crucial factors affecting service quality. In addition, good communication between healthcare professionals and patients' families is also regarded as essential to creating a holistic and patient-centered service. Conclusions: The quality of nursing services in home health care depends on various factors, including nurse competency, effective communication, and family involvement. Managerial support and supportive policies are also essential to ensure that nurses can deliver optimal care. This research provides valuable insight for developing training programs and policies to enhance the quality of home nursing services.